Tindak Tutur Perlokusi Dalam Novel Guru Aini Karya Andrea Hirata Dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia - Mintarsih, Mimin; Wiyanti, Endang; Atmapratiwi, Heppy (PT. Lancar Media Komunikasi, 2023)
ABSTRACT A perlocutionary speech act is an utterance uttered by a speaker that often has influence or effect on the listener. This effect or power of influence is intentionally or unintentionally created by the speaker. The method used in this research is a descriptive method with a qualitative approach. Based on this research, it can be seen that there are types of perlocutionary speech acts, namely non-commissive speech acts with 2 findings with a percentage of 3.08%, directive perlocutionary speech acts with 27 findings with a percentage of 41.53%, perlocutionary speech acts with a percentage of 4 declarations. 6, 15%, expressive perlocutionary speech acts were 22 findings with a percentage of 33.85 and representative perlocutionary speech acts were 10 findings with a percentage of 15.38%. From the data obtained, it can be concluded that the types of perlocutionary speech acts, namely directive speech acts and expressive speech acts, have a greater number compared to other types of perlocutionary speech acts in the novel.